2000
DOI: 10.1002/(sici)1097-0223(200001)20:1<51::aid-pd755>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and outcome in sacrococcygeal teratomas: a review of cases between 1992 and 1998

Abstract: A review of sacrococcygeal teratomas diagnosed in the antenatal period in the West Midlands region over a six year interval is reported. The aim of the study was to assess the contribution of ultrasound scanning to the management of cases and to determine the outcome of prenatally diagnosed sacrococcygeal teratomas. A retrospective review of 10 cases was performed to obtain pregnancy details, ultrasound scan data and outcome information. Two fetuses were electively aborted. Perinatal mortality was 62.5% in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Type III SCTs, as described by Altman, are characterized by a predominantly pelvic mass extending to the abdomen and perineum, in contrast to type I and II lesions, which are predominantly external on the perineum and type IV lesions that are entirely pelvic (Altman et al, 1974). SCTs are predominantly found in females with a 4 : 1 ratio while lymphangiomas are seen predominantly in males with a ratio of 5 : 1 (Brace et al, 2000;Konen et al, 2002). Although SCTs are the most common congenital tumor with an incidence of 1 : 35 000 births (Brace et al, 2000) intra-abdominal lymphangiomas are rarer occurrences, with only 10 reported cases of prenatal detection, 3 of which ended with termination of the pregnancy owing to rapid growth of the tumors (Deshpande et al, 2001;Ho et al, 2002;Konen et al, 2002;Groves et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type III SCTs, as described by Altman, are characterized by a predominantly pelvic mass extending to the abdomen and perineum, in contrast to type I and II lesions, which are predominantly external on the perineum and type IV lesions that are entirely pelvic (Altman et al, 1974). SCTs are predominantly found in females with a 4 : 1 ratio while lymphangiomas are seen predominantly in males with a ratio of 5 : 1 (Brace et al, 2000;Konen et al, 2002). Although SCTs are the most common congenital tumor with an incidence of 1 : 35 000 births (Brace et al, 2000) intra-abdominal lymphangiomas are rarer occurrences, with only 10 reported cases of prenatal detection, 3 of which ended with termination of the pregnancy owing to rapid growth of the tumors (Deshpande et al, 2001;Ho et al, 2002;Konen et al, 2002;Groves et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This fetal demise is usually related to the development of large arteriovenous shunts within the tumor leading to fetal hydrops. SCTs also carry a high perinatal mortality rate ranging from 12 to 68%, with the greatest mortality in those with extensive abdominal or pelvic involvement (Avni et al, 2002;Brace et al, 2000). Larger, more vascular tumors are at increased risk of intra-tumoral hemorrhage at any time, both in-utero and at the time of delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor size and growth rate as well as its histological (mature/immature) and component type (solid/cystic/mixed) may be risk factors of tumors related to the vital prognosis. [6][7][8][9][10][11][12][13][14][15][16] In contrast, as risk factors in children, heart failure and fetal edema are related to mortality. 17 Recommendation: For tumor lesions outside the pelvis, it is reasonable to consider cesarean section depending on the size thereof in order to avoid tumor rupture, tumor hemorrhaging and delivery difficulty.…”
Section: Guideline Formulation Methodsmentioning
confidence: 99%
“…The main reason for the poor prognosis in fetal SCT is high-output cardiac failure caused by increased blood flow, according to the amount of solid component present in the tumor, and rupture of the tumor during delivery with a massive hemorrhage. 3 Few large multicenter surveys on both the prenatal and postnatal courses of SCT have been performed. In 2009, the Japanese SCT Study Group was established with the support of a grant from The Ministry of Health, Labour and Welfare of Japan (H21-23 Health and Labour Sciences Research Grants for Research on Intractable Diseases).…”
mentioning
confidence: 99%